(untitled) (Tạp chí Y học Cộng đồng, 2022)
Background: The development of a vaccine against COVID-19 infection is on the way. However, opinions on the implementation of the vaccine and the needs to receive the COVID-19 vaccine vary considerably among people, which might influence the future demand forecast and pricing considerations for COVID-19 vaccine. Objectives: This study aims at 1) describing the demand and ability to pay, and 2) analysing factors associated with participants; intention to utilize the COVID-19 vaccine of medical students. Subjects and methods: We conducted a cross-sectional study among Hanoi Medical University students. Logistic regression was used to describe the correlation between COVID-19 vaccination needs and related factors. Linear regression was used to describe the correlation between the ability to pay for the COVID-19 vaccine and some associated factors. Results: Nearly 80% of the participants reported that they were willing to get vaccinated against COVID-19 if a vaccine were available. Factors associated with students’ needs to accept the COVID-19 vaccine included worry about COVID-19 and the year of study of participants. The average price that people accept to pay for a vaccine against COVID-19 is 485.25 ± 418.64 thousand VND. Conclusion: In this study, many students aaalikely get vaccinated, and the need to uptake COVID-19 vaccine was considered to be associated with worry of COVID-19 and year of study.